1998
DOI: 10.1364/ao.37.000170
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic probes with improved excitation and collection efficiency for deep-UV Raman and resonance Raman spectroscopy

Abstract: The ability of ultraviolet resonance Raman spectroscopy (UVRRS) to determine structural, environmental, and analytical information concerning low-concentration aqueous biomolecules makes it a powerful bioanalytical and biophysical technique. Unfortunately, its utility has been limited by experimental requirements that preclude in situ or in vivo studies in most cases. We have developed the first high-performance fiber-optic probes suitable for long-term use in pulsed UVRRS applications in the deep- UV (DUV, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…We have developed a fiber-optic probe configuration that overcomes the effects of sample self-absorption using a unique geometry (as illustrated in Figure 2b) where the collection volume includes the entire excited sample volume near the tip of the excitation fiber (8). Here, the collection efficiency is optimized for resonance Raman experiments where virtually all the signal derives from a small region immediately distal to the excitation fiber tip because the excitation light is almost completely absorbed within about one probe diameter from the tip.…”
Section: Fiber-optic Probes For Uvrrs In Aqueous Environmentsmentioning
confidence: 99%
“…We have developed a fiber-optic probe configuration that overcomes the effects of sample self-absorption using a unique geometry (as illustrated in Figure 2b) where the collection volume includes the entire excited sample volume near the tip of the excitation fiber (8). Here, the collection efficiency is optimized for resonance Raman experiments where virtually all the signal derives from a small region immediately distal to the excitation fiber tip because the excitation light is almost completely absorbed within about one probe diameter from the tip.…”
Section: Fiber-optic Probes For Uvrrs In Aqueous Environmentsmentioning
confidence: 99%
“…21,22 Briefly, the fiber-optic probe assembly consists of a single excitation fiber (600 µm in diameter) into which light from the frequency-doubled argon ion laser is coupled. At the probe end, light diverges from the endface in a roughly 19°truncated cone (defocused beam); the excitation fiber is surrounded by six collection fibers (each 400 µm in diameter) that collect the scattered radiation at 90°from the axis of the excitation fiber from roughly 100 nl of sample volume adjacent to the excitation fiber tip.…”
Section: Uv Resonance Raman Spectroscopymentioning
confidence: 99%
“…For enzyme spectra, the probe consisted of one 600 µm core diameter excitation fiber cleaved perpendicular to the fiber axis at each end and six collection fibers of 400 µm core diameter with 45°mirrors at the distil end which were fabricated as previously described. 27 Each collection fiber was aligned individually such that the inside surface of the mirror faced the illuminated volume and the bottom of the mirror was ¾130 µm below the plane of the cleaved face of the excitation fiber which improves collection efficiency (unpublished results). The use of a 600 µm excitation fiber allows for up to eight immediately adjacent 400 µm collection fibers, but because the collection fibers are necessarily offset from the excitation fiber, only six were employed and arranged around the excitation fiber in two groups of three as shown in Fig.…”
Section: Optical Fiber Probementioning
confidence: 99%
“…However, we have previously demonstrated that fiber-optic probes can also be designed to efficiently deal with this sample self-absorbance issue and which offer the additional advantage of in situ measurement capability. 26,27 The utility of conventional UVRRS configurations for investigating photo-labile analytes is further constrained by the need to focus the excitation light to a spot size comparable to the spectrometer slit-width because of signal throughput considerations. In order to achieve adequate spectral resolution, slit widths (and hence spot sizes) of ca.…”
Section: Introductionmentioning
confidence: 99%